Description Of Student Caring Code Stikes Academic Stage Ners Program Santa Elisabeth Medan Year 2022 - Mestiana Br Karo; Helinida Saragih; Elida Rezki Gratia Hutabarat (Jurnal EduHealth, 2023)
Caring Code is a guide that was developed as a guide in implementing caring behavior. Students are the forerunner of future leaders. Caring is a part that reflects the values ​​in the development of individual behavior and can describe a person's identity, and caring behavior is not only on a person's ability to do or accept his current condition, but has an impact on self-acceptance in the future. The purpose of this study was to find out the description of the Caring Code for the Students of the Nursing Study Program at the Academic Stage of STIKes Santa Elisabeth Medan 2022. This type of research was a descriptive research design. Sampling in this study using total sampling, respondents as many as 333 people. The results showed that the caring code of students in the good category were 62 respondents (79,5%) for level I nurses, 51 respondents for level II nurses (68,9%), level III nurses 61 respondents (71,8%) and level IV nurses 62 respondents (64.6%). It is hoped that the results of this study can increase knowledge and information about how to apply good caring so that it can improve caring behavior to students and it is also expected to be able to conduct seminars on caring code to STIKes Santa Elisabeth Medan students.